Taxation Reforms and Changes in Revenue Assignments in China - Singh, Raju.; Ahmad, Ehtisham; Lockwood, Ben. (Washington, D.C. : International Monetary Fund, 2004)
The value-added tax (VAT) in China has the unusual feature that capital goods are included in the VAT base. In addition, most services are subject to the business tax, which is not creditable against VAT, but which accrues to local governments, and operates as a turnover tax. On grounds of economic efficiency, it would be desirable to eliminate these distortions so that domestic producers are not increasingly placed at a disadvantage as China dismantles tariff and nontariff barriers on competing goods. Reforming indirect taxation would however generate considerable revenue losses for local governments and, in the absence of any compensatory mechanisms, there would be significant impediments to the needed reforms. This paper focuses on the extent of revenue losses, their distribution across provinces, and possible options for compensation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet